SOCIAL-PHILOSOPHICAL ASPECTS OF FORMING A CULTURE OF HEALTHY THINKING IN YOUTH - Atakulov Mavlonbek Saitkulovich (Western European Studies, 2024)
In our country, the issues of forming a culture of healthy lifestyle in the thinking of young people and protecting the health of citizens are of the most urgent state importance. In particular, as one of the most important directions of the process of economic, social, political and spiritual-ideological reforms, in particular, of reforms in the country's education system, it is aimed at the issue of bringing up a mentally healthy and physically mature generation.
Keywords: issue; physically; mentally